The important role of safety culture in the management of major industrial accidents - Siti Noraishah, Ismail; Azizan, Ramli; Eka Prasetya, Tofan Agung (Faculty of Public Health, Universitas Airlangga, Indonesia, 2024)
Major industrial accidents or disasters can have significant impacts on various aspects, including human health, the environment, societal well-being, and national economies. The concept of safety culture is increasingly receiving attention as a means of mitigating industrial mishaps. Nonetheless, a dearth of comprehensive systematic reviews exists that specifically examine the important role of safety culture in effectively mitigating severe industrial accidents across diverse industries on a global scale. Hence, the primary aim of this research is to examine the important role of safety culture in the effective management of industrial accidents across diverse sectors. Method: The systematic literature review (SLR) from the ScienceDirect database was established using the four basic procedures outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A total of thirty-three scholarly publications were retrieved from the database, encompassing the years 2017 to 2021, which specifically address the important role of safety culture in the effective management of major industrial incidents. Results: The findings yielded two primary themes, namely, the significance of safety culture at both the managerial and employee levels. These topics were then categorised into ten subthemes. The findings indicate that safety culture exerts a significant influence at the managerial level in mitigating industrial accidents through the enhancement of safety training. Conclusion: In summary, a safety culture holds significant importance within the realm of management as it serves to effectively mitigate the occurrence of industrial accidents in the years to come.